An Unexpected Regulatory Cascade Governs a Core Function of the Drosophila PRC1 Chromatin Protein Su(z)2. Issue 2 (1st February 2017) - Nguyen, Son C; Yu, Stephanie; Oberlick, Elaine; Wu, Chao-ting
Abstract: Polycomb group (PcG) proteins are major chromatin-bound factors that can read and modify chromatin states to maintain gene silencing throughout development. Here we focus on a close homolog of the PcG protein Posterior sex combs to better understand how these proteins affect regulation. This homolog, called Suppressor 2 of zeste [Su(z)2] is composed of two regions: the N-terminal homology region (HR), which serves as a hub for protein interactions, and the C-terminal region (CTR), which is believed to harbor the core activity of compacting chromatin. Here, we describe our classical genetic studies to dissect the structure of Su ( z ) 2 . Surprisingly, we found that the CTR is dispensable for viability. Furthermore, the core activity of Su(z)2 seems to reside in the HR instead of the CTR. Remarkably, our data also suggest a regulatory cascade between CTR and HR of Su(z)2, which, in turn, may help prioritize the myriad of PcG interactions that occur with the HR.